Transformation of Women's Social Education in the GWF (Grab Women Fighter) Community in Makassar City: A Sociological Study of Emancipatory Learning in the Digital Workspace - Sangaji, Ayu Indira; Syukur, Muhammad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the transformation of women's social education within the GWF (Grab Women Fighter) community in Makassar City as a form of emancipatory learning in the digital workplace. Using a qualitative approach and case study method, this study examines how social interactions and daily practices in the digital community shape critical awareness and women's empowerment. Data were obtained through online observations, in-depth interviews, and documentation of community activities. The results show that the GWF (Grab Women Fighter) community in Makassar City has become an arena for non-formal social learning that fosters solidarity, self-reflection, and digital adaptability. The emancipatory learning process occurs through the practice of sharing experiences, emotional support, and reflection on gender and economic inequality. This research contributes to the development of studies in the sociology of education by highlighting the importance of digital space as an arena for inclusive and emancipatory social education.